Primary Health Care: the Relational Aspects of Social Interaction between Family Doctors and People with Disabilities - Rupšienė, Liudmila; Saveljeva, Regina; Batuchina, Aleksandra (Social Welfare: Interdisciplinary Approach, 2024)
Strategic documents of the United Nations and the European Union express the belief that primary health care is a fundamental part of health care services and it must be accessible to all people and funded according to the means. Many research studies prove that enhancement of the primary health care system helps to effectively eliminate causes and risk factors for poor health and to prevent likely impairment of health in the future. However, the data of recent investigations demonstrate that the quality of health care services in Lithuania is much poorer than the average of the EU, and the institution of family doctors providing services of this type suffers from problems related to the efficiency of functioning. Therefore, it is worth investigating possible causes for this problem, to identify them and search for solutions. The paper presents the research that is aimed at examining one part of the aspects of the problem, specifically the relational aspects of social interaction between family doctors and people with disabilities from the point of view of people with disabilities and their relatives. 555 people with disabilities (PWD) and 540 respondents who had relatives with disabilities and took care of them (PWDcare) participated in the survey carried out in 2019–2020 and reported about their experience of social interaction with family doctors. The research indicated many positive tendencies, of which the most prominent was the satisfaction of the relationship, trust and understandment with family doctors. But at the same time the research revealed some more problematic areas, such as the lack of family doctors’ compassion and warmth to many patients. These results are important for improving the primary health care service and quality as well for strengthening the family doctors’ education.
Keywords: health care service; social interactions; healthcare quality; family doctor; people with disabilities